Genetic Study of the Effect of the Toxoplasma gondii on Somatic Cells of the Bone Marrow in Female Mice and a treatment Attempt by Laurus Nobilis Leaf Extract - Ghfran Shihab Ahmed Al-badri1, Aysir Salih Mohammed2 , Omar Raheem Khalaf2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
This study aimed to find out the ability of T. gondii parasite to induce genetic changes in the bone marrowcells of female mice and to try therapeutically for it using bay leaf extract. The parasite was extracted from(23) placentas for aborted women and injected into the 42 mice with an average weight of (20-30) gram. Itwas divided into six groups at a rate of (3 females) per group. The first group doses the oil only as a negativecontrol, the second group was infected with the parasite as a positive control, while the four study groupsdose the plant extract of the bay leaves for (14) days and at doses of (15, 10, 5, 1) mg. for Kg after a periodof infestation with the parasite for 14 days. The results of the chromosomal changes showed the type ofchromatid fracture among the females injected with the parasite + the extract and with all its concentrationssignificantly reduce the level at (P <0.05). The concentration was 15 mg/kg, the lowest as the results reached(9.33 ± 1.33) compared to the control of the parasite (44.00 ± 2.30), while the centromere fracture showedAll concentrations showed a significant decrease at the level of (p<0.05) and showed concentrations 15and 10 more decreases with a result of 2.66 ± 1.33 for both concentrations compared to the control of theparasite, As for the annular chromosome, all concentrations showed a significant decrease at the level of(p<0.05) for females injected with the parasite extract, and the concentration was 15 mg/kg, the lowest was(6.66 ± 1.33) compared to the control of the parasite.